Vision Affects Gait Speed but not Patterns of Muscle Activation During Inclined Walking—A Virtual Reality Study - Benady, Amit; Zadik, Sean; Ben-Gal, Oran; Cano Porras, Desiderio; Wenkert, Atalia; Gilaie-Dotan, Sharon; Plotnik, Meir (Frontiers in Bioengineering and Biotechnology, 2021)
While walking, our locomotion is affected by and adapts to the environment based on vision- and body-based (vestibular and proprioception) cues. When changing to downhill walking we modulate gait by braking to avoid uncontrolled acceleration, and when changing to uphill walking we exert effort to avoid deceleration. In this study we aimed to measure the influence of visual inputs on this behavior and on muscle activation. Specifically, we aimed to explore whether the gait speed modulations triggered by mere visual cues after transitioning to virtually inclined surface walking are accompanied by changes in muscle activation patterns typical to those triggered by veridical (gravitational) surface inclination transitions. We used an immersive virtual-reality system equipped with a self-paced treadmill and projected visual scenes that allowed us to modulate physical-visual inclinations congruence parametrically. Gait speed and leg muscle electromyography were measured in 12 healthy young adults. In addition, the magnitude of subjective visual verticality misperception (SVV) was measured by the rod and frame test. During virtual (non-veridical) inclination transitions vision modulated gait speed by (i) slowing down to counteract the excepted gravitational ‘boost’ in virtual downhill inclinations and by (ii) speeding up to counteract the expected gravity resistance in virtual uphill inclinations. These gait speed modulations were reflected in muscle activation intensity changes and associated with SVV misperception. However, temporal patterns of muscle activation were not affected by virtual (visual) inclination transitions. Our results delineate the contribution of vision to locomotion and may lead to enhanced rehabilitation strategies for neurological disorders affecting movement.